Current Understanding and Clinical Management of Meniere's Disease: A Systematic Review - Perez-Carpena, Patricia; Lopez-Escamez, Jose A. (Seminars in Neurology, 2020)
Meniere's disease (MD) is a set of uncommon disorders with core phenotype of tinnitus, episodic vertigo, and sensorineural hearing loss. MD shows a genetic predisposition and a family history is found in 10% cases, with an autosomal dominant inheritance pattern. It is a multifactorial condition whose onset and development are triggered by the combined effect of genetic and environmental factors. Histopathological studies have associated MD with the accumulation of endolymph in the cochlea and the vestibular organs. However, endolymphatic hydrops does not fully explain the persistence of tinnitus, hearing loss progression, or the frequency of vertigo attacks.There are several comorbidities associated with MD, such as migraine, anxiety, autoimmune, and autoinflammatory disorders, adding more complexity to the phenotype. This “extended phenotype” can make the diagnosis and clinical management more complex, but it could also lead to a better characterization, understanding, and treatment of MD patients.We have conducted a systematic review on MD to update current knowledge, focusing on its mechanisms, diagnosis, comorbidities, and practical management.
Keywords: Meniere's disease; endolymphatic hydrops; sensorineural hearing loss; vertigo; tinnitus